A study with focus on course and outcome of delayed neurological deterioration in mild head injury patients - Sachin Dhakad; Abhilash Singh; Kumar Deepak; Pruthviraj CS; Rashmi Thakur; Vinod Yedalwar; Sonpal Jindal (Asian Journal of Medical Sciences, 2023)
Background: Mild head injury (MHI) complicated by an intracranial hemorrhage (ICH) is a common cause of hospital admission after head trauma. The majority of patients get non-operative care, maintain neurological stability, and are successfully discharged. However, a small proportion of people experience delayed neurological deterioration (DND). The characteristics of DND following an MHI exacerbated by ICH are poorly understood. Aims and Objectives: The study was conducted to evaluate the temporal course and outcome of MHI patients with respect to DND. Materials and Methods: A prospective study was performed on all adult patients presenting over 15 consecutive months with MHI. Patients who were treated conservatively after initial head computed tomography and had a subsequent DND (Glasgow Coma Scale score decrease ≥2) were identified. Demographics, neurological status, clinical and temporal course, radiographic findings, and outcome data were collected. Results: Over 15 months, 150 patients with MHI were included in the study for observation; of these, 49 patients experienced DND. 31.33% of patients deteriorated within 24 h after admission. 14 patients (9.37%) died. Variables significantly associated with mortality included age >60 years delayed presentation at tertiary center, progressive intracranial bleed, or increase in cerebral edema. Conclusion: The incidence of DND after MHI with ICH is low and usually occurs within 24 h after admission. It results in significant morbidity and mortality if it is the result of progressive ICH. Further research is needed to identify risk factors that can allow early detection and improve outcomes in these patients